Development of pemphigus vegetans and exacerbation of pemphigus foliaceus after secukinumab loading in a patient with complicated generalized pustular psoriasis and pyoderma gangrenosum - Minai, Lisa; Takeichi, Takuya; Ogawa, Youichi; Honobe‐Tabuchi, Akiko; Okamoto, Takashi; Mitsui, Hiroshi; Shimada, Shinji; Akiyama, Masashi; Kawamura, Tatsuyoshi (Journal of dermatology, 2023)
In dermatology, biologics that block signaling pathways of TNF‐α, IL‐4/IL13, IL‐17s, and IL‐23 are widely used for the treatment of several inflammatory skin diseases, such as atopic dermatitis and psoriasis. They have shown excellent efficacy with an acceptable safety profile. However, these biologics targeting pathogenic cytokines and their receptors could modulate immunological balance, leading to the development of other inflammatory or autoimmune skin diseases in some cases. In this study, we present a patient who suffered pemphigus vegetans and showed an exacerbation of pemphigus foliaceus after secukinumab loading for the treatment of complicated generalized pustular psoriasis and pyoderma gangrenosum.